2022
DOI: 10.2298/psi210301005k
|View full text |Cite
|
Sign up to set email alerts
|

The time, the path, its length and strenuousness in maze learning

Abstract: Previous findings show that rats in a maze tend to choose the shortest path to reach food. But it is not clear whether this choice is based on path length solely, or some other factors. The aim of this experiment was to investigate which factor dominates the behavior in a maze: path (longer and shorter), time (longer and shorter), or effort (more or less strenuous). The experiment involved 40 mice (4 groups), learning a maze with two paths. Each group went through only one of the situations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The heatmap analysis suggests that the differences do lie in the learning process especially for the IL-12 Mo group—indeed both old groups learned to climb the wall during the learning stage. Kostić & Tošković (2022) designed an experiment to determine which factor among path, time and effort was the key determinant of rodent behavior in exploring a maze to reach food, and they found that the subject always chose paths requiring less effort. Their findings provided a clue for why the older rats had attempted to climb the wall to reach the food-box—this may be less arduous for them compared with young rats.…”
Section: Discussionmentioning
confidence: 99%
“…The heatmap analysis suggests that the differences do lie in the learning process especially for the IL-12 Mo group—indeed both old groups learned to climb the wall during the learning stage. Kostić & Tošković (2022) designed an experiment to determine which factor among path, time and effort was the key determinant of rodent behavior in exploring a maze to reach food, and they found that the subject always chose paths requiring less effort. Their findings provided a clue for why the older rats had attempted to climb the wall to reach the food-box—this may be less arduous for them compared with young rats.…”
Section: Discussionmentioning
confidence: 99%
“…Only accurate trials were used for the analysis of RT, ET, E, and TErr. Given that pilot results indicated a signi cant difference between performance of participants on the two mazes, and that the pilots reported feeling that one maze is harder than another, we included Group (group 1: trained on the hard maze, vs group 2: trained on the easy maze) as a factor in our analyses 94 for a parametrization of how a maze path can in uence navigation in mice). We further calculated Inverse E ciency scores (IE 95 ).…”
Section: Behavioural Analysismentioning
confidence: 99%